Determinants of Carbon Dioxide Emissions and Their Peaking Prospect: Evidence From China - Zhao, Huiqing; Hu, Jian; Hao, Feng; Zhang, Hongyuan (Frontiers in Environmental Science, 2022)
In order to examine the key determinants of carbon dioxide emissions and judge whether China's carbon dioxide emissions can reach their peak value before 2030, this paper first uses the extended STIRPAT model to analyze the determinants of China's carbon dioxide emissions from 1995 to 2019, and then uses the model regression result to forecast the carbon dioxide emissions from 2020 to 2040 under six scenarios to investigate their prospect. It is found that population size, GDP per capita, energy intensity, share of coal consumption, urbanization level, share of secondary industry and investment have significant positive effects on carbon dioxide emissions. Among them, the influence of population size is the biggest, and energy intensity is the weakest. China’s carbon dioxide emissions can reach their peak in 2029 under the baseline scenario. Increasing the rate of population growth, energy intensity and share of coal consumption will push back the peak year. A lower rate of economic growth and share of secondary industry will bring the peak year forward. Therefore, it is necessary to optimize the industrial structure and energy consumption structure, reduce the energy intensity and control the population size in order to achieve the goal of peaking carbon dioxide emissions as soon as possible.